Improved colonization of East African highland Musa tissue culture plants by endophytic Fusarium oxysporum - Paparu, P.; Dubois, T.; Gold, C.; Niere, B.; Adipala, E.; Coyne, D. (Informa UK Limited, 2006)
Non-pathogenic endophytic Fusarium oxysporum inoculated into banana (Musa spp.) tissue culture plants can provide protection against banana weevils (Cosmopolites sordidus) and nematodes (Radopholus similis). The degree of control probably depends, in part, upon the level of endophyte establishment following inoculation. In this study, we compared three methods of inoculating endophytic fungi into eight week-old tissue culture plants: (1) Dipping the roots and rhizomes in a spore suspension, (2) dipping the roots and rhizomes in a spore suspension after the plants had been grown in an additional nutrient solution to enhance root growth, and (3) using a solid substrate inoculum after plants were grown in an additional nutrient solution. Irrespective of the inoculation method, rhizomes were colonized to a higher extent (91%) than roots (64%). The use of a solid substrate inoculum resulted in a higher percentage root colonization (96%) than when plants were dipped in a spore suspension. When roots and rhizomes were dipped in a spore suspension, root colonization was higher (71%) for plants grown in an additional nutrient solution than for plants obtained directly from rooting medium (49%). Use of a solid substrate inoculum and increased root development by growing the plants in a nutrient solution are necessary to maximize root colonization by fungal endophytes.